Extensive Spinal Epidural Abscess Resulting in Complete Paraplegia Treated by Selective Laminectomies and Irrigation. Issue 9 (22nd June 2022) - Xu, Tongshuai; Du, Yukun; Guo, Jianwei; Li, Jianyi; Shao, Cheng; Shi, Changfang; Ren, Xianfeng; Xi, Yongming
Abstract : Background: Spinal epidural abscess (SEA) is an uncommon clinical entity that is often subject to delayed diagnosis and suboptimal treatment. Untreated disease leads to compression of the spinal cord, resulting in devastating complications. Case Presentation: A 56‐year‐old man visited our hospital for progressive lower back and lower extremity pain of several days' duration. Significant pyrexia (39.5°C) and elevated C‐reactive protein (89.2 mg/L) were detected during admission, but no positive neurological examination findings were observed. Magnetic resonance imaging revealed pyogenic discitis at L3–4. Despite the administration of directed antibiotic therapy, the patient's condition rapidly deteriorated, culminating in complete paraplegia secondary to an extensive SEA from L4 to C7. Emergency spinal decompression surgery was canceled due to his poor clinical condition and refusal of informed consent. After further deterioration, he consented to two‐level selective laminectomies and irrigation. Conclusions: In contrast with prior case reports, this case illustrates the natural history of an extensive SEA during conservative and late surgical treatment. Early diagnosis and timely surgical decompression are of great importance for extensive SEA. Abstract : This study reports a rare case of an extensive spinal epidural abscess caused by methicillin‐resistant Staphylococcus aureus . The patient was initially treated with directed antibiotic therapy and refused consent for an emergency spinal decompression; consequently, we were able to observe his clinical course without early surgical intervention. Furthermore, we believe that our study makes a significant contribution to the literature because when consent was eventually granted for surgery, we used a safe and effective adapted surgical technique of selective laminectomy and irrigation, despite his significantly compromised clinical condition.